Copper hydroxide nanosheets: Synthesis, structural analysis, and electrochemical performance evaluation - Hye Seong Jang; Min Kyeong Kim; Dohun Lee; Youngji Kim; Yeongeun Jang; Seunghwa Lee; John Hong; Gyeong Hee Ryu (Applied Surface Science Advances, 2025)
Two-dimensional (2D) oxides have garnered extensive attention owing to their remarkable properties, including high surface-to-volume ratios and unique chemical and physical properties. Among the various methods reported for the synthesis of 2D structures, surfactant-based approaches are particularly advantageous because they enable the formation of 2D nanostructures at the water–air interface. Nanostructured copper oxides are widely used as electrode materials for energy storage and conversion in batteries and supercapacitors. We synthesised 2D Cu(OH)2 nanosheets using an innovative surfactant-assisted method and analysed their structural and electrochemical properties. The Cu(OH)2 nanosheets exhibited good supercapacitor performance because of the increased active area of the 2D structures. However, the electrochemical performance of the Cu(OH)2 nanosheets was adversely affected by annealing owing to the changes in the crystal structure of copper hydroxide. Our findings contribute significantly to the field of 2D nanoscale materials, and the proposed synthesis method facilitates the development of various nanoscale materials with tuneable properties.